Analisis Miskonsepsi Siswa pada Materi Hukum Newton di Kelas X IPA SMA Negeri 1 Berastagi - Estavina Br. Sitepu; Muhammad Yakob (Jurnal Pendidikan Fisika dan Sains, 2019)
In physics learning the teacher usually explains with the lecture method without explaining and linking it to daily life and that makes students misconceptions and misconceptions that cause misconceptions. Physics learning in high school is currently experiencing a lot of problems because students find it difficult to understand physics lessons or material delivered by the teacher. The purpose of this study was to determine students' misconceptions of Newton's Law material in class X IPA of SMA Negeri 1 Berastagi. The research method used descriptive qualitative. This research was conducted with a population of research is class X IPA SMA Negeri 1 Berastagi, Samples were taken randomly (random sampling) and selected class X IPA 2 as many as 30 students as research classes. The results showed that there was a misconception in Newton's Law material in class X IPA 2 of SMA Negeri 1 Berastagi. Misconceptions on Newton's Law material are divided into 3 criteria: high, medium and low. Based on the data analysis the average percentage of students' misconceptions in Newton's Law material is high criteria as much as 89.3%. The average percentage of students' misconceptions on Newton's Law material is 50%. The average percentage of students' misconceptions on Newton's Law criteria is as low as 28.6%. It is recommended for further researchers not only to examine the existence of misconceptions in students but also to examine the causes of misconceptions that arise, types of misconceptions, and also how to overcome misconceptions. To minimize misconceptions the teacher should change the method, a clearer learning model so that students understand more and not be mistaken in understanding concepts. Keywords : Misconception, Certainty of Response Index (CRI)